2017
DOI: 10.1161/circulationaha.116.024261
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma Ceramides, Mediterranean Diet, and Incident Cardiovascular Disease in the PREDIMED Trial (Prevención con Dieta Mediterránea)

Abstract: Background Although in vitro studies and investigations in animal models and small clinical populations have suggested that ceramides may represent an intermediate link between over-nutrition and certain pathological mechanisms underlying cardiovascular disease (CVD), no prospective studies have investigated the association between plasma ceramides and risk of CVD. Methods The study population consisted of 980 participants from the PREDIMED trial, including 230 incident cases of CVD and 787 randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
235
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(256 citation statements)
references
References 82 publications
(66 reference statements)
14
235
3
4
Order By: Relevance
“…In addition, recent analysis of subjects in the PREDIMED (Prevention with Mediterranean Diet) trial, who were at high cardiovascular risk, indicated that C24:0, C22:0, and C16:0 ceramides were positively associated with prevalent and incident CVD 16. By contrast, we find the C24:0/C16:0 ceramide ratio is inversely associated with the coronary risk factors of age and smoking status and also inversely associated with prevalent CVD in both FHS and SHIP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent analysis of subjects in the PREDIMED (Prevention with Mediterranean Diet) trial, who were at high cardiovascular risk, indicated that C24:0, C22:0, and C16:0 ceramides were positively associated with prevalent and incident CVD 16. By contrast, we find the C24:0/C16:0 ceramide ratio is inversely associated with the coronary risk factors of age and smoking status and also inversely associated with prevalent CVD in both FHS and SHIP.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of the sphingolipid ceramide impairs insulin action, is a modulator of mitochondrial and ER stress, promotes apoptosis, and potentially links CV disease, insulin resistance, low‐grade inflammation, and PD. In a study of participants in the prospective Prevención con Dieta Mediterránea trial, plasma ceramide concentrations were linked to nonfatal acute MI, nonfatal stroke, and CV death . PD is also associated with altered sphingolipid metabolism .…”
Section: Contributions From the Basic Sciencesmentioning
confidence: 99%
“…Hepatic ceramide concentrations were measured by the Metabolomics Platform at the Broad Institute (Cambridge, Massachusetts, USA) as previously described (60,61). Livers were harvested 6 hours after food removal, and the hepatic lipids were extracted from liver homogenates using isopropanol containing N-heptadecanoyl-d-erythro-sphingosine (Avanti Polar Lipids) as an internal standard.…”
Section: Animals and Experimental Induction Of Er Stress Male Pctp +mentioning
confidence: 99%